ChemInform Abstract: Dehydrogenation of Perfluoroalkyl Ketones by Using a Recyclable Oxoammonium Salt. Issue 45 (14th October 2013) - Hamlin, Trevor A.; Kelly, Christopher B.; Leadbeater, Nicholas E.
Abstract This reaction is specific to perfluoroalkyl ketones.